2010
DOI: 10.1111/j.1467-9299.2009.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Political Change Affect Senior Management Turnover? An Empirical Analysis of Top-Tier Local Authorities in England

Abstract: In many political systems the political neutrality of senior managers’ tenure is often cherished as a key part of the politics‐administration dichotomy and is subject to formal safeguards. We test hypotheses about the impact of political change on senior management turnover drawn from political science, public administration and private sector management theory. Using panel data to control for unobserved heterogeneity between authorities, we find that changes in political party control and low organizational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
(48 reference statements)
2
43
1
1
Order By: Relevance
“…Consequently there are authors who stress KPI design in order to align the tactical and strategic level reporting and planning (e.g. Brignall, 1993;Boland and Fowler, 2000;Boyne et al, 2010;Dalehite, 2008;Irwin, 2002;Jones, 2004;McAteer and Orr, 2006). Furthermore there are authors, who have seen KPI frameworks as tools that help local entities to change, for example towards continuous improvement (Batac and Carassus, 2009;Caiden, 2006;Hoque, 2005;Kloot, 1997;Kloot and Martin, 2000;Light, 1997;Rashman and Radnor, 2005).…”
Section: Multiple Institutional Logics and Kpismentioning
confidence: 99%
“…Consequently there are authors who stress KPI design in order to align the tactical and strategic level reporting and planning (e.g. Brignall, 1993;Boland and Fowler, 2000;Boyne et al, 2010;Dalehite, 2008;Irwin, 2002;Jones, 2004;McAteer and Orr, 2006). Furthermore there are authors, who have seen KPI frameworks as tools that help local entities to change, for example towards continuous improvement (Batac and Carassus, 2009;Caiden, 2006;Hoque, 2005;Kloot, 1997;Kloot and Martin, 2000;Light, 1997;Rashman and Radnor, 2005).…”
Section: Multiple Institutional Logics and Kpismentioning
confidence: 99%
“…Again using CPA data, Boyne et al. () found that senior management turnover increased when change of political control of an English local authority interacted with low organizational performance. When our survey was conducted, we observed that there had been managerial turnover in the worst UoR performers, with respondents there emphasizing the commitment to improvement rather than disputing the scores awarded in earlier rounds.…”
Section: Discussion and Interpretation Of The Findingsmentioning
confidence: 99%
“…For the opposition, there is not much reward in identifying high performance. It is exposing and blaming low performance that may initiate a shift in attention and a policy renewal (Jones and Baumgartner, 2005), change of senior management or top executive (Boyne et al, 2010) or eventually bring the opposition into the ministerial seats after the next election. In some instances, it is also important for the ruling government to identify and prevent low performance.…”
Section: Discussionmentioning
confidence: 99%
“…Incumbents in local authorities with poor performance got a reduced aggregate vote share in the election after the publication of the performance information, but there was not a similar increase in aggregate vote share for incumbents in local authorities with high performance. Boyne et al (2010) found that information on low service performance affected senior management team turnover and, under certain conditions of simultaneous change in political control, also top executive succession in local governments. This may indicate that performance information matters but information on poor performance matters most.…”
Section: Introductionmentioning
confidence: 99%